Emblematics and metaphor: theoretical facets and hermeneutic issues - Borgogni, Daniele (Frontiers in Communication, 2023)
The article focuses on Renaissance emblematics and its privileged relationship with metaphor, considered in the light of contemporary theories as an inherently tensional form, steeped in interchange and transition and heavily relying on a basically conflictual dynamic. Though often dismissed as an academic, antiquarian form of figurality or as a pleasing symbolical form steeped in monologic stability, emblematics was in fact conceived as a brand-new hybrid textual mode whose complex interplay of signs favored multiplied discursive models and the constant relay between visual and textual elements, between abstract conceptualization and thoughts-made-visible. The paper, in other words, will try to reassess and re-evaluate emblematics as a profoundly plural form of communication whose connections with metaphor were much deeper and qualitatively different than it is usually thought. This slant approach to what is conventionally considered a tame example of early modern textuality highlights, on the contrary, its idiosyncratic meaning procedures: the metaphorical conceptualizations of emblematic compositions were not necessarily based on similarity and testify to their cognitive potential which ushered in an idea of communication as projective and dislocating, as a dialogic space allowing for the paradoxical copresence of ideological consistency and its deconstruction.